Small opacities among dental laboratory technicians in Copenhagen. Issue 5 (May 1988) - Sherson, D; Maltbaek, N; Olsen, O
Abstract : After a case of advanced pneumoconiosis occurred in a dental laboratory technician, 31 other dental technicians and 30 control subjects controlled for smoking habits, sex, and age were investigated. More technicians (55%) than controls (30%) had at least grade 1 dyspnoea (p greater than 0.05). Multiple regression analysis showed that 13 technicians who had produced dental prostheses for at least 15 years had consistently lower lung function (FVC, FEV1, FEV1/FVC, MEF50, and DCO single breath), although the differences were not statistically significant. All mean lung function values for technicians and controls were within normal limits. Increases in MEF50 after breathing 80% helium and 20% O2 failed to show small airways dysfunction among the technicians. Of the six with radiological pneumoconiosis (5 simple, 1 advanced) four had symptoms. All three biopsy specimens showed varying degrees of pulmonary fibrosis. DCO single breath was diminished in four of the six. One male dental technician had scleroderma and possibly Erasmus syndrome. Blind readings showed an increased number of suspicious chest x rays films (greater than or equal to category 0/1) among older smokers and ex-smokers (p = 0.013) regardless of occupation. Our results support other evidence that dental technicians are at risk of developing pneumoconiosis. Therefore, adequate hygienic control of dental laboratories is indicated.